Penguatan Sistem Pengawasan Terintegrasi dalam Penyelenggaraan Rumah Subsidi Bagi Masyarakat Berpenghasilan Rendah di Kabupaten Buleleng - Sriyadnya, Nyoman (Program Studi PPKn Jurusan Hukum dan Kewarganegaraan Undiksha Singaraja, 2026)
This article examines the strengthening of an integrated supervision system in the implementation of subsidized housing for low-income communities (MBR) in Buleleng Regency. The main problem lies in the weak and unintegrated supervision system, characterized by fragmented authority among institutions, the absence of standardized operating procedures (SOP), and the lack of physical verification before subsidy disbursement. This study applies a qualitative descriptive approach through field observation, document analysis, and stakeholder discussions. The findings reveal that weak supervision results in inconsistencies in housing development, poor housing quality, and inadequate protection for beneficiaries. Therefore, it is recommended to establish a Regent Regulation that includes technical guidelines, SOPs, and the formation of a cross-sector supervisory team to enhance accountability, housing quality, and the effectiveness of subsidized housing programs in a sustainable manner.